A North Sea and Baltic Sea Model Ensemble Eutrophication Assessment - Almroth, Elin (Springer Netherlands, 2010)
A method to combine observations and an ensemble of ecological models is suggested to produce a eutrophication assessment. Using threshold values and methodology from the Oslo and Paris Commissions (OSPAR) and the Helsinki Commission (HELCOM), four models are combined to assess eutrophication for the Baltic and North Seas for the year 2006. The assessment indicates that the entire southeastern part of the North Sea, the Kattegat, the Danish Straits, the Gulf of Finland, and the Gulf of Riga as well as parts of the Arkona Basin, the Bornholm Basin, and the Baltic proper may be classified as problem areas. The Bothnian Bay and parts of the Baltic proper, the Bornholm Basin, and the Arkona Basin are classified as potential problem areas. This method is a useful tool for the classification of eutrophication; however, the results depend on the threshold values, and further work is needed within both OSPAR and HELCOM to harmonize these values.